Outcome of management of congenital diaphragmatic hernia (Bangladesh Medical Journal Khulna, 2015)
Congenital Diaphragmatic Hernia (CDH) is a defect in the dome of diaphragm, more often in left and postero-lateral that permits the herniation of abdominal contents into the thorax. The lungs hypoplasia, pulmonary hypertension and persistent foetal circulation are important determinant of survival. The incidence is